3x=5x+6(2-x)

Simple and best practice solution for 3x=5x+6(2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x=5x+6(2-x) equation:


Simplifying
3x = 5x + 6(2 + -1x)
3x = 5x + (2 * 6 + -1x * 6)
3x = 5x + (12 + -6x)

Reorder the terms:
3x = 12 + 5x + -6x

Combine like terms: 5x + -6x = -1x
3x = 12 + -1x

Solving
3x = 12 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
3x + x = 12 + -1x + x

Combine like terms: 3x + x = 4x
4x = 12 + -1x + x

Combine like terms: -1x + x = 0
4x = 12 + 0
4x = 12

Divide each side by '4'.
x = 3

Simplifying
x = 3

See similar equations:

| 125x=17.50x+3.50 | | 7+2y=24 | | 6.3m+5=66 | | 0.04(y-8)+0.20y=0.06y-0.5 | | (x-3)(x-3)(x-3)-25=0 | | 4+2(3x-5)=3x+11 | | -6(0)+3y=-12 | | 5x^2=19x^2-12 | | 15=L-6 | | 260=2x-6+x+3 | | -6x^2-18x= | | 12(1.5-t)=42t | | y=-1/2(1)-1 | | 6X^2+62X=-44 | | y=-1/2(2)-1 | | 21+6b=7(3-6b) | | -3+1(-24)=-5 | | 18-5-4a=-36 | | 8x+15=81 | | 2c+7+c=14+3c+21 | | -2+2x=0 | | -3x+(-24)=-5 | | 20b=-6 | | 4x+4.5=5x-4.5 | | 6(-6+3n)=-90 | | 4+10h=3b-25 | | -36-x=-2x | | -2p+8=6-(8p+2) | | 9=7-2x | | -2+5x=16+8 | | 6x^4+6x-42=0 | | -6(2x-2)=-12x+12 |

Equations solver categories